Purification and characterization of phytase from rat intestinal mucosa - Yang, W J; Matsuda, Y; Sano, S; Masutani, H; Nakagawa, H (Biochimica et biophysica acta, 1991)
Phytase (myo-inositol hexakisphosphate phosphohydrolase; EC. 3.1.3.8 or 3.1.26) was purified from rat intestinal mucosa. The purified enzyme preparation exhibited two protein bands on SDS-polyacrylamide gel electrophoresis with estimated molecular masses of 70 kDa and 90 kDa. Rabbit antisera prepared against the 90K subunit cross-reacted with the 70K subunit on immunoblotting. The peptide maps of the 70K and 90K subunits were similar, and the N-terminal amino acid sequences of the two subunit proteins were almost identical. Treatments to remove sugar moieties from the proteins showed that the two subunit proteins had different oligosaccharide chains, although the difference in their molecular masses was not due to the difference in their oligosaccharide compositions. The purified enzyme also showed activity of alkaline phosphatase (orthophosphoric monoester phosphohydrolase; EC 3.1.3.1), but the properties of the two enzyme activities were different; the optimum pH for phytase activity was 7.5, while that for alkaline phosphatase was 10.4. Phytase activity did not necessarily require divalent cations, while Mg 2+ was essential for alkaline phosphatase activity. Phenylalanine, a specific inhibitor of intestine-type alkaline phosphatase had no effect on the phytase activity.